Effects of cassava pubescene on the behaviour, postembryonic development and reproduction of the cassava mealybug, Phenacoccus manihoti matileferrero (Homoptera: pseudococcidae) - Kasu, T.; Odebiyi, J.; Lema, K. (Springer, 1989)
Role of trichome density in cassava resistance to mealybug, Phenacoccus manihoti Matile-Ferrero was evaluated on the apex, the first expanded leaf and the stem in pubescent and glabrous cassava varieties. Pubescence significantly retarded the rate of settling and establishment of P. manihoti. The weight of the developing larvae was also affected becoming more pronounced at the pre-ovipositing adult stage. However, the relationship between pubescence and P. manihoti weight was not significant. Moreover, the significant differences in weight at the preovipositing adult stage was not reflected in the corresponding fecundity on the glabrous and pubescent varieties. Pubescence accounted for only 18% of the differences in observed fecundity. There was also no significant difference in the development period of the mealybug on glabrous and pubescent varieties. Pubescence appeared to be a mechanical irritant only.